GENDER CONSTRUCTION ON BANYUWANGI’S LEGEND - Dania, Maya (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2011)
Legend is a folktale that has a historical root or ground. It is interesting to investigate a legend since it is closely related with culture. Banyuwangi has a very nice legend that tells about the origin of its name. The legend is told in three different versions and each of them shares the same ending by the death of the woman in each story caused by her own husband.Suspiciously, a legend may be loaded with the gender construction that influences the society. It pictures a tangible differentiation between the image and the role from women and men. This paper aims to compares the three versions of the legend and analyses them using feminism point of view. Feminism movement nowadays is widening its movement to investigate the text which is suspected to support the patriarchy power. This paper uses literature research as its method and meets the result as follows: 1) In the legend’s first version, woman was stereotyped as the domestic worker, 2) In the legend’s second version, woman was portrayed as the second sex, 3) In the legend’s third version, woman is seen as a sexual object.Keywords: Banyuwangi legends, gender construction, feminism.